THE IMPORTANCE OF HUMOR IN JOURNALISTIC DISCOURSE - Rokhat Rakhmatullaevna Davranova (International Journal of Literature and Language Studies, 2026)
Humor has become an increasingly important element of modern journalistic discourse, serving not only as a source of entertainment but also as a powerful communicative and pragmatic tool. This article examines the significance of humor in journalism and its role in enhancing audience engagement, facilitating the interpretation of complex issues, and promoting critical reflection on social and political events. Using a qualitative approach and discourse analysis of journalistic texts, the study investigates how humor functions within news reports, opinion articles, satirical publications, and digital media platforms. The findings indicate that humor contributes to greater reader involvement, improves information retention, and enables journalists to address sensitive topics more effectively. At the same time, the study highlights the necessity of balancing humor with journalistic ethics and credibility. The article concludes that humor plays a vital role in contemporary journalism by strengthening communication between media institutions and audiences while fostering critical public discourse.